Analisis Pengaruh Entrepreneurial Leadership dan Motivasi Kerja Terhadap Kinerja Karyawan PT Tiga Putra Adhi Mandiri - Fransiska, Nike; Hutomo, Karyana (Binus Business Review, 2014)
The purpose of this study is to discover and understand how much the influence of entrepreneurial leadership and working motivation on employee performance at PT Tiga Putra Adhi Mandiri. This study used quantitative approach which used survey method with questionnaire as a tool to get the data, where the populations were 46 respondents. The analysis method that is used in this study is simple regression and multiple regressions. These analyses is used to find out how much the influence of entrepreneurial leadership and working motivation variables as independent variable on employee performance at PT Tiga Putra Adhi Mandiri as a dependent variable. The result of this study is entrepreneurial leadership had 40,3% significant influence on employee performance at PT Tiga Putra Adhi Mandiri and motivation also had 40,8% significant influence on employee performance at PT Tiga Putra Adhi Mandiri. While both entrepreneurial leadership and working motivation had 47,3%. Significant influence on employee performance at PT Tiga Putra Adhi Mandiri. Seeing each variable had significant influence then researcher recommend to increase the entrepreneurial leadership and working motivation so that the employee performance also increases and the company goal can be achieved.